Comparison of HLA-mismatched unrelated donor transplantation with post-transplant cyclophosphamide versus HLA-haploidentical transplantation in patients with active acute myeloid leukemia - Baron, Frédéric; Labopin, Myriam; Tischer, Johanna; Ciceri, Fabio; Raiola, Anna Maria; Blaise, Didier; Sica, Simona; Vydra, Jan; Fanin, Renato; Diez-Martin, Jose Luis; Bulabois, Claude Eric; Stölzel, Friedrich; et al. (Bone marrow transplantation, 2022)
HLA-haploidentical allogeneic hematopoietic stem cell transplantation (Haplo-HCT) is frequently used as treatment for patients with active acute myeloid leukemia (AML). Here, we investigated whether 9/10 HLA-mismatched unrelated donor transplantation (MMUD-HCT) with post-transplant cyclophosphamide (PTCy) is an adequate alternative. Inclusion criteria in this retrospective registry study consisted of adult patients, first HCT with a Haplo donor or MMUD between 2010 and 2020 using PTCy as graft-versus-host disease (GVHD) prophylaxis, and primary refractory or relapsed disease. MMUD patients were pair-matched 1 to 2 with Haplo-recipients. A total of 73 MMUD patients met the inclusion criteria. Their data were compared to those of 146 Haplo patients in a matched-pair analysis. Median follow-up was 27 months in MMUD patients and 36 months in Haplo recipients. Two-year incidences of relapse and non-relapse mortality (NRM) were 40% and 18% in MMUD patients, respectively, versus 50% (P = 0.23) and 24% (P = 0.18) in Haplo recipients. Two-year leukemia-free survival (LFS) and overall survival (OS) was 42% and 46% in MMUD recipients, respectively, versus 26% (P = 0.1) and 28% (P = 0.061) in Haplo-patients. In conclusions, in AML patients with active disease at transplantation, MMUD-HCT results in at least comparable outcomes to Haplo-HCT when PTCy is applied.
Keywords: Leukemia, Myeloid, Acute; transplantace hematopoetických kmenových buněk; Humans; Transplantation, Haploidentical; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; příprava pacienta k transplantaci; dospělí; lidé; Unrelated Donors; haploidentická transplantace; Adult; nepříbuzný dárce; nemoc štěpu proti hostiteli; Retrospective Studies; Transplantation Conditioning; Cyclophosphamide; retrospektivní studie; cyklofosfamid; akutní myeloidní leukemie